The Relationship between Nutritional Adequacy Level and Nutritional Status among School-going Adolescents in West Aceh - Ranita Suri Dewi (Universitas Teuku Umar, 2026)
The triple burden of malnutrition is the primary nutritional problem experienced by many adolescents. This condition is triggered by unhealthy consumption patterns, a sedentary lifestyle, low economic status, and poor nutritional knowledge. Methods. This study employed a cross-sectional approach with a sample of 312 school-going adolescents in West Aceh. It aimed to examine the differences in the level of nutritional adequacy and its relationship with the nutritional status of adolescents in urban and rural areas. The instruments used were a 2x24-hour food recall questionnaire and anthropometric measurements using BIA scales and a microtoise. Statistical analysis used Spearman's rank correlation and the Mann-Whitney test. Results. The results showed the level of energy and carbohydrate adequacy was different significantly between adolescents in rural and urban areas (p>0.05). There was a significant positive relationship between the level of carbohydrate adequacy and BAZ among adolescents in both rural and urban areas (p<0.05). Conclusion. The level of energy adequacy is not related to BAZ, but the level of carbohydrate adequacy is significantly related to BAZ between adolescents in rural and urban areas. Nutrition interventions should focus on balanced carbohydrate consumption rather than simply increasing food quantity.